PENGARUH BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING FINANCING (NPF), DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OJK PERIODE 2019-2023 - Ditto Taruna Sakti; Vivi Adeyani Tandean (Journal Accounting International Mount Hope, 2024)
This research was made to test the Operational Cost on Operational Revenues (BOPO), Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR) in sharia banks listed on the OJK for the 2019-2023 period. This type of research uses a quantitative approach with data sources, namely secondary data. The population in its research is sharia banks listed on the OJK. The researcher used data analysis techniques with the statistical application of IBM SPSS Statistics 29. The application was used to carried out Research Hypothesis Testing. The output of the research, the BOPO hs a partially negative and significant effect on Profitability, FDR has a partially positive significant effect on Profitability. Meanwhile, NPF has no partial effect on Profitability. Furthermore, the BOPO, NPF, and FDR have a simultaneously effect on Profitability.